Monstrous Women in Middle English Romance - Urban, Misty. (The Edwin Mellen Press, 2010)
This study treats the appearance of the monstrous woman in Middle English romance narratives as a self-conscious literary trope that reflects on, and often criticizes, the grounds of philosophical, cultural, and narrative discourse that place women both inside and outside medieval culture, constructing them as Other by biological and social difference yet relying on them for the reproduction and healthy maintenance of the male-governed social order. Building on current monster theory and adding to research on medieval women in literature, this study reclaims the Middle English romance as a sop
Description based upon print version of record.
Keywords: English literature – Middle English; 1100-1500 – History and criticism.; Monsters in literature.; Romances; English – History and criticism.; Women in literature.; Romances; English; English literature; Women in literature; Monsters in literature; English; Languages & Literatures; English Literature